RELEVANCE OF THE PROBLEM OF SOCIAL SELF-DETERMINATION OF ADOLESCENTS IN THE CONTEXT OF MODERN CHALLENGES - Lyashchenko, Tetyana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article analyzes the scientific and pedagogical literature regarding the characteristics of the content of the concepts of “self-determination” and “social self-determination”. The purpose of the research is to outline the characteristics of adolescents’ social self-determination in the context of contemporary realities. This goal involves addressing the following tasks: refining the concepts of “self-determination” and “social self-determination”; characterizing factors that influence adolescents’ social self-determination; presenting survey results on the activities of out-of-school education institutions amid wartime challenges; and exploring the potential of extracurricular institutions to foster adolescents’ social self-determination. To achieve this objective, the following scientific research methods are employed: theoretical (analysis of scientific and pedagogical literature on the essence of the concepts of “self-determination” and “social self-determination”, systematization, and generalization of information); empirical (online surveys); and statistical (analysis and interpretation of the research statistical data).Adolescence is considered the most sensitive period for human socialization, characterized by the formation of value orientations that determine the content of activities and the direction of individual activity. Emphasis is placed on the need for each person to develop their position and attitude to the events occurring in society and the country. The peculiarities of social self-determination of teenagers in the context of modern realities are highlighted. It is found that social self-determination is a dynamic process of finding one’s position in the system of social relations. In adolescence, this process involves the formation of an individual's worldview, the assimilation of social roles, and the mastery of a particular set of role functions, which ensure the readiness of adolescents to make conscious independent choices in life.The factors influencing the social self-determination of adolescents are characterized: by the family, which can create a deep influence on the entire complex of the child’s physical and spiritual life; peers, who provide not only social interaction but also influence the formation of social skills; mass media as a source of new knowledge and patterns of behaviour; educational institutions as a socio-pedagogical system that ensures the formation and realization of personality.The peculiarities of the activities of out-of-school education institutions in the conditions of military challenges have been revealed. Their role in self-realizing and developing pupils’ creative potential has been clarified. An analysis of the research results on the influence of out-of-school education institutions’ activities on the individual’s social self-determination is carried out. The importance and demand of out-of-school education institutions in the conditions of martial law have been proven: along with the organization of meaningful leisure time, teachers of out-of-school education institutions carry out public and educational work, provide psychological support to participants in the educational process and help them adapt to new realities. Attention is focused on the fact that out-of-school educational institutions’ activities contribute to teenagers’ creative activity, creating conditions for individual self-realization and social self-determination.